Molecular Dynamic of Pinostrobin and Pinocembrin from Kaempferia pandurata Roxb. towards Estrogen Receptor Positive (ESR) and Estrogen Receptor Negative (VEGFR) of Breast Cancer - Fadilah, Fadilah (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: This research was conducted to simulate the molecular dynamic of pinocembrin and pinostrobin against erythrocyte sedimentation rate and estimated glomerular filtration rate protein. Materials and Methods: In this study, the interaction of pinostrobin and pinocembrin as key compounds of Kaempferia pandurata toward ER and vascular endothelial growth factor (VEGF) as a molecular marker of estrogen receptor positive and ER negative (ERâˆ’) of breast cancer. The simulation was done by molecular docking and dynamic simulation. The molecular docking was conducted using AutoDock 4.2, while the dynamic simulation using AMBER 14 software. Results: Analysis of dynamics simulation was done by considering the root mean square deviation (RMSD), Root Mean Square Fluctuation, hydrogen bonding conditions, and MM-PBSA calculation. The dynamic simulation result showed that pinocembrin chalcone compounds have less free energy than pinostrobin. Conclusion: Pinostrobin and pinocembrin can interact with ER and VEGF, having a potential for specific ERâˆ’ treatment.